The impacts of open data initiatives on smart cities - Neves, Fátima Trindade (2022)
Neves, F. T., de Castro Neto, M., & Aparicio, M. (2020). The impacts of open data initiatives on smart cities: A framework for evaluation and monitoring. Cities, 106, 1-15. [102860]. https://doi.org/10.1016/j.cities.2020.102860